Crohn’s disease recurrence updates: first surgery vs. surgical relapse patients display different profiles of ileal microbiota and systemic microbial-associated inflammatory factors - Russo, Edda; Cinci, Lorenzo; Di Gloria, Leandro; Baldi, Simone; D’Ambrosio, Mario; Nannini, Giulia; Bigagli, Elisabetta; Curini, Lavinia; Pallecchi, Marco; Andrea Arcese, Donato; Scaringi, Stefano; Malentacchi, Cecilia; et al. (Frontiers in Immunology, 2022)
Background and aims: Crohn’s Disease (CD) pathogenesis is still unclear. Remodelling in mucosal microbiota and systemic immunoregulation may represent an important component in tissue injury. Here we aim to characterize the ileal microbiota in both pathological and healthy settings and to evaluate the correlated systemic microbial-associated inflammatory markers comparing first time surgery and relapse clinical conditions. Methods: We enrolled 28 CD patients at surgery; we collected inflamed and not inflamed mucosa tissues and blood samples from each patient. Bacterial wall adherence was observed histologically while its composition was assessed through amplicon sequencing of the 16S rRNA gene. In addition, we evaluated the systemic microRNA (miRNA) by Quantitative real-time PCR amplification and Free fatty acids (FFAs) using Gas Chromatography- Mass Spectroscopy Results: The total number of mucosal adherent microbiota was enriched in healthy compared to inflamed mucosa. The other way around, the phylum Tenericutes, the family of Ruminococcaceae, and the genus Mesoplasma and Mycoplasma were significantly enriched in pathological setting. Significant microbiota differences were observed between relapse and first surgery patients regarding the family of Bacillaceae 2 and Brucellaceae, the genera of Escherichia/Shigella, Finegoldia, Antrobacter, Gemmatimonas, Moraxella, Anoxibacillus, and Proteus. At systemic level, we observed a significant downregulation of circulating miR-155 and miR-223, as well as 2-methyl butyric, isobutyric and hexanoic (caproic) acids in recurrence compared to first surgery patients. In addition, the level of hexanoic acid seems to act as a predictor of recurrence risk in CD patients (OR 18; 95% confidence interval 1.24-261.81; p=0.006). Conclusions: We describe a dissimilarity of ileal microbiota composition comparing CD and healthy settings, as well as systemic microbial-associated inflammatory factors between first surgery and surgical relapse. We suggest that patterns of microbiota, associated with healthy ileal tissue, could be involved in triggering CD recurrence. Our findings may provide insight into the dynamics of the gut microbiota-immunity axis in CD surgical recurrence, paving the way for new diagnostics and therapeutics aimed not only at reducing inflammation but also at maintaining a general state of eubiosis in healthy tissue.